Composite liquid cement grinding aid and preparation method thereof
By adopting a composite liquid cement grinding aid, combined with polymer grinding aid solution, modified sodium lignin sulfonate, modified triethanolamine, composite surfactant components and silane coupling agent dispersion components, the problems of poor dispersion and poor performance of cement grinding are solved, and the effect of efficient grinding and improving the physical properties of cement is achieved.
Patent Information
- Application Number
- CN202411758494.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-07
AI Technical Summary
The existing cement aids have poor dispersibility and are unable to effectively improve cement performance, resulting in low grinding efficiency and poor physical performance.
Compound liquid cement grinding aids are used, and the composition includes polymer grinding aids solution, modified sodium lignin sulfonate, modified triethanolamine, composite surfactant components and silane coupling agent dispersion components to improve grinding efficiency and improve the physical properties of cement through synergistic effects.
It significantly improves the grinding efficiency and physical properties of cement, improves the dispersion and stability of cement particles, extends the service life of grinding equipment, and improves the hardening performance and strength of cement.
Smart Images

Figure BDA0005166966660000101 
Figure BDA0005166966660000111 
Figure BDA0005166966660000112
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cement grinding aids, and in particular to a composite liquid cement grinding aid and a preparation method thereof. Background Art
[0002] In the cement production process, grinding is an indispensable key link. Its efficiency and quality directly affect the final performance and application effect of cement products. In traditional cement grinding technology, physical or chemical methods are often used to improve grinding efficiency and improve the physical properties of cement by adding grinding aids. However, with the rapid development of the cement industry and the intensification of market competition, the performance requirements for cement grinding aids are becoming higher and higher.
[0003] Traditional cement grinding aids are mostly single components, such as lignin sulfonate, triethanolamine, etc. Although they can improve the grinding efficiency to a certain extent, they have problems such as poor dispersibility, insufficient stability, and limited improvement in the physical properties of cement. In order to solve these problems, technicians in this field began to explore the preparation and application of composite cement grinding aids. Composite cement grinding aids are usually composed of multiple functional components, which can significantly improve the grinding efficiency and improve the physical properties of cement through synergistic effects. However, in the preparation process of composite cement grinding aids, there are still many challenges in the selection and proportion of raw materials, optimization of preparation process, etc. Therefore, how to develop a composite cement grinding aid with good dispersibility and the ability to improve cement performance has become a technical problem that needs to be solved urgently by technicians in this field. Summary of the invention
[0004] Technical issues solved
[0005] In view of the above-mentioned shortcomings of the prior art, the present invention provides a composite liquid cement grinding aid and a preparation method thereof, which can effectively solve the problem that the cement grinding aid of the prior art has poor dispersibility and cannot improve cement performance.
[0006] Technical Solution
[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions:
[0008] A composite liquid cement grinding aid, the composite liquid cement grinding aid is composed of the following components: a polymer grinding aid solution, modified sodium lignin sulfonate, modified triethanolamine, a composite surfactant component and a silane coupling agent dispersion component;
[0009] The polymer grinding aid solution is prepared with maleic anhydride, triethanolamine, acrylic acid and isopentenyl polyoxyethylene ether as raw materials;
[0010] The modified sodium lignin sulfonate is prepared by inserting a diethanolamine group into the structure of sodium lignin sulfonate;
[0011] The modified triethanolamine is prepared by reacting succinic acid and triethanolamine as main raw materials;
[0012] The composite surfactant component is prepared by reacting butyltriphenylphosphonium bromide and sodium dodecylbenzenesulfonate as main raw materials.
[0013] Furthermore, the preparation steps of the polymer grinding aid solution are:
[0014] Step a, add 10g of maleic anhydride into a flask, stir in a water bath at 50°C until it melts, then add 15g of triethanolamine dropwise at a rate of 1 drop / s, keep warm in a water bath at 50°C for 2h, and cool to room temperature to obtain the functional monomer component;
[0015] Step b, dissolving 11 g of acrylic acid in 20 g of deionized water, stirring until completely dissolved, the result is recorded as acrylic acid solution, dissolving 0.1 g of ammonium persulfate in 5 g of deionized water, stirring until completely dissolved, the result is recorded as initiator solution;
[0016] Step c, add 60g of isopentenyl polyoxyethylene ether and 60g of deionized water into a flask, stir and dissolve in a 60°C water bath, and then simultaneously add the functional monomer component, acrylic acid solution and initiator solution at a rate of 2 drops / s. After keeping warm for 3 hours, the result is a polymer grinding aid solution.
[0017] Furthermore, the stirring speed for stirring until melting in step a is 500 r / min, the stirring speed for stirring until complete dissolution in step b is 300 r / min, and the stirring and dissolving operation in step c is stirring at a stirring speed of 200 r / min for 30 minutes.
[0018] Furthermore, the preparation steps of the modified sodium lignin sulfonate are:
[0019] Step 1, add 10g sodium lignin sulfonate and 20g deionized water into a flask, stir thoroughly and add 11g diethanolamine, the result after ultrasonic treatment is recorded as the component to be reacted;
[0020] Step 2, heat the components to be reacted to 70°C in a water bath and add 25g of formaldehyde solution at this temperature at a rate of 1 drop / s, reflux at a constant temperature for 2h, then cool to 45°C, remove deionized water by rotary evaporation, wash with anhydrous ethanol and filter to remove excess diethanolamine, dry the filter cake and grind it through a 200-mesh sieve to obtain modified sodium lignin sulfonate.
[0021] Furthermore, the operation of fully stirring in step 1 is stirring at a stirring speed of 400 r / min for 10 minutes, the operation of ultrasonic treatment in step 1 is ultrasonic dispersion at a frequency of 26 kHz for 15 minutes, the temperature of rotary evaporation in step 2 is 68° C., and the operation of drying in step 2 is drying in a vacuum drying oven at 60° C. for 12 hours.
[0022] Furthermore, the preparation method of the modified triethanolamine is:
[0023] Weigh the calculated amount of succinic acid and triethanolamine in a molar ratio of 1:3 and pour them into a flask. Add sulfuric acid solution dropwise under a water bath condition of 70-80°C to adjust the pH value to 4-5. After constant temperature reaction for 3-4 hours, cool to room temperature, add sodium hydroxide solution dropwise to adjust the pH value to 7, and the resulting product is modified triethanolamine.
[0024] Furthermore, in the preparation method of modified triethanolamine, the mass fraction of the sulfuric acid solution is 10%, and the mass fraction of the sodium hydroxide solution is 15%.
[0025] Furthermore, the preparation method of the composite surfactant component is:
[0026] Weigh 5 g of butyltriphenylphosphonium bromide and 55 g of deionized water, mix them, add 4 g of sodium dodecylbenzenesulfonate, stir at a stirring speed of 600 r / min for 4 hours, let it stand for separation, and take out the lower layer of viscous liquid, which is the composite surfactant component.
[0027] Furthermore, the preparation method of the silane coupling agent dispersion component is:
[0028] Weigh 3-5g of silane coupling agent KH-550 and disperse it in 200ml of deionized water. Stir at a stirring speed of 600r / min for 20min to obtain the silane coupling agent dispersion component.
[0029] A method for preparing a composite liquid cement grinding aid, the preparation method comprising:
[0030] 12-15 parts by weight of modified sodium lignin sulfonate are added to 100 parts by weight of silane coupling agent dispersion component, and after ultrasonic dispersion at a frequency of 28 kHz for 30 minutes, 35-40 parts by weight of polymer grinding aid solution, 8-10 parts by weight of modified triethanolamine and 3-5 parts by weight of composite surfactant component are added, and the mixture is stirred at a stirring speed of 500 r / min for 30 minutes to obtain a composite liquid cement grinding aid.
[0031] Beneficial Effects
[0032] The present invention provides a composite liquid cement grinding aid and a preparation method thereof. Compared with the prior art, the present invention has the following beneficial effects:
[0033] Firstly, the polymer grinding aid solution of the present invention uses maleic anhydride, triethanolamine, acrylic acid and isopentyl polyoxyethylene ether as raw materials. The reaction product of maleic anhydride and triethanolamine can form a compound with special functional groups. These functional groups can be effectively adsorbed on the surface of cement particles, reduce the friction between particles, and improve the grinding efficiency. The addition of acrylic acid and isopentyl polyoxyethylene ether can further enhance the dispersibility and stability of the grinding aid, make the cement particles more easily dispersed in water, reduce the agglomeration phenomenon, and be beneficial to the refinement of cement particles. The present invention modifies the sodium lignin sulfonate by accessing a diethanolamine group. On the basis of retaining the original dispersibility of the sodium lignin sulfonate, a new functional group is introduced, which can enhance the interaction between the sodium lignin sulfonate and the cement particles, further improve the grinding aid effect, and the modified sodium lignin sulfonate can also effectively adjust the setting time of cement to prevent grinding difficulties caused by too fast setting.
[0034] Secondly, the modified triethanolamine prepared by using succinic acid and triethanolamine as raw materials has extremely strong polarity and reactivity, can form a protective film on the surface of cement particles, reduce the wear of cement particles during grinding, and promote the uniform dispersion of cement particles. The modified triethanolamine can also react with calcium ions in cement to form a stable compound, which helps to improve the hardening performance and strength of cement. Butyltriphenylphosphonium bromide has excellent dispersibility and wettability, can effectively reduce the surface tension between cement particles, and promote the dispersion of cement particles. Sodium dodecylbenzene sulfonate has good The foaming property and decontamination ability of the composite surfactant can further enhance the dispersing effect of the grinding aid. The combination of the two enables the composite surfactant component to play a dual role in the cement grinding process, which not only improves the grinding efficiency but also improves the physical properties of cement. The addition of silane coupling agent KH-550 enables the grinding aid to form a strong chemical bonding layer on the surface of cement particles, which can not only enhance the bonding force between cement particles, but also improve the strength and durability of cement. At the same time, the silane coupling agent can also effectively prevent the cement particles from falling off and breaking during the grinding process, protect the grinding equipment and extend its service life. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] The present invention will be further described below in conjunction with the embodiments.
[0037] Example 1
[0038] A composite liquid cement grinding aid of this embodiment, the composite liquid cement grinding aid is composed of the following components: a polymer grinding aid solution, modified sodium lignin sulfonate, modified triethanolamine, a composite surfactant component and a silane coupling agent dispersion component;
[0039] The polymer grinding aid solution is prepared from maleic anhydride, triethanolamine, acrylic acid and isopentenyl polyoxyethylene ether as raw materials, and the preparation steps are as follows:
[0040] Step a, add 10g of maleic anhydride into a flask, stir at a stirring speed of 500r / min in a water bath at 50°C until it melts, then add 15g of triethanolamine dropwise at a dropping speed of 1 drop / s, and keep the mixture in a water bath at 50°C for 2h after the dropping is completed. After cooling to room temperature, the obtained mixture is recorded as a functional monomer component;
[0041] Step b, dissolving 11 g of acrylic acid in 20 g of deionized water, stirring at a stirring speed of 300 r / min until completely dissolved, the result obtained is recorded as an acrylic acid solution, and dissolving 0.1 g of ammonium persulfate in 5 g of deionized water, stirring until completely dissolved, the result obtained is recorded as an initiator solution;
[0042] Step c, add 60g of isopentenyl polyoxyethylene ether and 60g of deionized water into a flask, stir at a stirring speed of 200r / min for 30min in a water bath at 60°C, add functional monomer components, acrylic acid solution and initiator solution at the same time at a dropping rate of 2 drops / s, and keep the reaction warm for 3h to obtain a polymer grinding aid solution.
[0043] Modified sodium lignin sulfonate is prepared by inserting diethanolamine groups into the structure of sodium lignin sulfonate, and the preparation steps are as follows:
[0044] Step 1, add 10g sodium lignin sulfonate and 20g deionized water into a flask, stir at a stirring speed of 400r / min for 10min, then add 11g diethanolamine, and ultrasonically disperse at a frequency of 26kHz for 15min to obtain the resultant as the component to be reacted;
[0045] Step 2, heat the components to be reacted to 70°C in a water bath and add 25g of formaldehyde solution at this temperature at a rate of 1 drop / s, reflux at a constant temperature for 2h, then cool to 45°C, perform rotary evaporation at 68°C to remove deionized water, and then wash with anhydrous ethanol and filter to remove excess diethanolamine. The filter cake is placed in a vacuum drying oven at 60°C and dried for 12h, then ground through a 200-mesh sieve to obtain modified sodium lignin sulfonate.
[0046] Modified triethanolamine is prepared by reacting succinic acid and triethanolamine as main raw materials, and its preparation method is as follows:
[0047] Weigh the calculated amount of succinic acid and triethanolamine in a molar ratio of 1:3 and pour them into a flask. Add a 10% sulfuric acid solution by mass under a 70°C water bath to adjust the pH value to 4. After constant temperature reaction for 3 hours, cool to room temperature, add a 15% sodium hydroxide solution by mass to adjust the pH value to 7 to obtain modified triethanolamine.
[0048] The composite surfactant component is prepared by reacting butyltriphenylphosphonium bromide and sodium dodecylbenzenesulfonate as main raw materials, and the preparation method thereof is as follows:
[0049] Weigh 5 g of butyltriphenylphosphonium bromide and 55 g of deionized water, mix them, add 4 g of sodium dodecylbenzenesulfonate, stir at a stirring speed of 600 r / min for 4 hours, let it stand for separation, and take out the lower layer of viscous liquid, which is the composite surfactant component.
[0050] The preparation method of the silane coupling agent dispersion component is as follows:
[0051] Weigh 3 g of silane coupling agent KH-550 and disperse it in 200 ml of deionized water. Stir at a stirring speed of 600 r / min for 20 min to obtain the silane coupling agent dispersion component.
[0052] A preparation method of a composite liquid cement grinding aid, the preparation method comprising:
[0053] To 100 parts by weight of the silane coupling agent dispersion component, 12 parts by weight of modified sodium lignin sulfonate were added, and after ultrasonic dispersion at a frequency of 28 kHz for 30 minutes, 35 parts of polymer grinding aid solution, 8 parts by weight of modified triethanolamine and 3 parts by weight of composite surfactant components were added, and the mixture was stirred at a stirring speed of 500 r / min for 30 minutes to obtain a composite liquid cement grinding aid.
[0054] Example 2
[0055] A composite liquid cement grinding aid of this embodiment, the composite liquid cement grinding aid is composed of the following components: a polymer grinding aid solution, modified sodium lignin sulfonate, modified triethanolamine, a composite surfactant component and a silane coupling agent dispersion component;
[0056] The polymer grinding aid solution is prepared from maleic anhydride, triethanolamine, acrylic acid and isopentenyl polyoxyethylene ether as raw materials, and the preparation steps are as follows:
[0057] Step a, add 10g of maleic anhydride into a flask, stir at a stirring speed of 500r / min in a water bath at 50°C until it melts, then add 15g of triethanolamine dropwise at a dropping speed of 1 drop / s, and keep the mixture in a water bath at 50°C for 2h after the dropping is completed. After cooling to room temperature, the obtained mixture is recorded as a functional monomer component;
[0058] Step b, dissolving 11 g of acrylic acid in 20 g of deionized water, stirring at a stirring speed of 300 r / min until completely dissolved, the result obtained is recorded as an acrylic acid solution, and dissolving 0.1 g of ammonium persulfate in 5 g of deionized water, stirring until completely dissolved, the result obtained is recorded as an initiator solution;
[0059] Step c, add 60g of isopentenyl polyoxyethylene ether and 60g of deionized water into a flask, stir at a stirring speed of 200r / min for 30min in a water bath at 60°C, add functional monomer components, acrylic acid solution and initiator solution at the same time at a dropping rate of 2 drops / s, and keep the reaction warm for 3h to obtain a polymer grinding aid solution.
[0060] Modified sodium lignin sulfonate is prepared by inserting diethanolamine groups into the structure of sodium lignin sulfonate, and the preparation steps are as follows:
[0061] Step 1, add 10g sodium lignin sulfonate and 20g deionized water into a flask, stir at a stirring speed of 400r / min for 10min, then add 11g diethanolamine, and ultrasonically disperse at a frequency of 26kHz for 15min to obtain the resultant as the component to be reacted;
[0062] Step 2, heat the components to be reacted to 70°C in a water bath and add 25g of formaldehyde solution at this temperature at a rate of 1 drop / s, reflux at a constant temperature for 2h, then cool to 45°C, perform rotary evaporation at 68°C to remove deionized water, and then wash with anhydrous ethanol and filter to remove excess diethanolamine. The filter cake is placed in a vacuum drying oven at 60°C and dried for 12h, then ground through a 200-mesh sieve to obtain modified sodium lignin sulfonate.
[0063] Modified triethanolamine is prepared by reacting succinic acid and triethanolamine as main raw materials, and its preparation method is as follows:
[0064] Weigh the calculated amount of succinic acid and triethanolamine in a molar ratio of 1:3 and pour them into a flask. Add a 10% sulfuric acid solution by mass under 80°C water bath conditions to adjust the pH value to 5. After constant temperature reaction for 4 hours, cool to room temperature, add a 15% sodium hydroxide solution by mass to adjust the pH value to 7 to obtain modified triethanolamine.
[0065] The composite surfactant component is prepared by reacting butyltriphenylphosphonium bromide and sodium dodecylbenzenesulfonate as main raw materials, and the preparation method thereof is as follows:
[0066] Weigh 5 g of butyltriphenylphosphonium bromide and 55 g of deionized water, mix them, add 4 g of sodium dodecylbenzenesulfonate, stir at a stirring speed of 600 r / min for 4 hours, let it stand for separation, and take out the lower layer of viscous liquid, which is the composite surfactant component.
[0067] The preparation method of the silane coupling agent dispersion component is as follows:
[0068] Weigh 5 g of silane coupling agent KH-550 and disperse it in 200 ml of deionized water. Stir at a stirring speed of 600 r / min for 20 min to obtain the silane coupling agent dispersion component.
[0069] A preparation method of a composite liquid cement grinding aid, the preparation method comprising:
[0070] 15 parts by weight of modified sodium lignin sulfonate were added to 100 parts by weight of silane coupling agent dispersion component, and ultrasonically dispersed at a frequency of 28 kHz for 30 minutes, and then 40 parts of polymer grinding aid solution, 10 parts by weight of modified triethanolamine and 5 parts by weight of composite surfactant component were added. After stirring at a stirring speed of 500 r / min for 30 minutes, the result was a composite liquid cement grinding aid.
[0071] Example 3
[0072] A composite liquid cement grinding aid of this embodiment, the composite liquid cement grinding aid is composed of the following components: a polymer grinding aid solution, modified sodium lignin sulfonate, modified triethanolamine, a composite surfactant component and a silane coupling agent dispersion component;
[0073] The polymer grinding aid solution is prepared from maleic anhydride, triethanolamine, acrylic acid and isopentenyl polyoxyethylene ether as raw materials, and the preparation steps are as follows:
[0074] Step a, add 10g of maleic anhydride into a flask, stir at a stirring speed of 500r / min in a water bath at 50°C until it melts, then add 15g of triethanolamine dropwise at a dropping speed of 1 drop / s, and keep the mixture in a water bath at 50°C for 2h after the dropping is completed. After cooling to room temperature, the obtained mixture is recorded as a functional monomer component;
[0075] Step b, dissolving 11 g of acrylic acid in 20 g of deionized water, stirring at a stirring speed of 300 r / min until completely dissolved, the result obtained is recorded as an acrylic acid solution, and dissolving 0.1 g of ammonium persulfate in 5 g of deionized water, stirring until completely dissolved, the result obtained is recorded as an initiator solution;
[0076] Step c, add 60g of isopentenyl polyoxyethylene ether and 60g of deionized water into a flask, stir at a stirring speed of 200r / min for 30min in a water bath at 60°C, add functional monomer components, acrylic acid solution and initiator solution at the same time at a dropping rate of 2 drops / s, and keep the reaction warm for 3h to obtain a polymer grinding aid solution.
[0077] Modified sodium lignin sulfonate is prepared by inserting diethanolamine groups into the structure of sodium lignin sulfonate, and the preparation steps are as follows:
[0078] Step 1, add 10g sodium lignin sulfonate and 20g deionized water into a flask, stir at a stirring speed of 400r / min for 10min, then add 11g diethanolamine, and ultrasonically disperse at a frequency of 26kHz for 15min to obtain the resultant as the component to be reacted;
[0079] Step 2, heat the components to be reacted to 70°C in a water bath and add 25g of formaldehyde solution at this temperature at a rate of 1 drop / s, reflux at a constant temperature for 2h, then cool to 45°C, perform rotary evaporation at 68°C to remove deionized water, and then wash with anhydrous ethanol and filter to remove excess diethanolamine. The filter cake is placed in a vacuum drying oven at 60°C and dried for 12h, then ground through a 200-mesh sieve to obtain modified sodium lignin sulfonate.
[0080] Modified triethanolamine is prepared by reacting succinic acid and triethanolamine as main raw materials, and its preparation method is as follows:
[0081] Weigh the calculated amount of succinic acid and triethanolamine in a molar ratio of 1:3 and pour them into a flask. Add a 10% sulfuric acid solution by mass under a 75°C water bath to adjust the pH value to 5. After constant temperature reaction for 3 hours, cool to room temperature, add a 15% sodium hydroxide solution by mass to adjust the pH value to 7 to obtain the modified triethanolamine.
[0082] The composite surfactant component is prepared by reacting butyltriphenylphosphonium bromide and sodium dodecylbenzenesulfonate as main raw materials, and the preparation method thereof is as follows:
[0083] Weigh 5 g of butyltriphenylphosphonium bromide and 55 g of deionized water, mix them, add 4 g of sodium dodecylbenzenesulfonate, stir at a stirring speed of 600 r / min for 4 hours, let it stand for separation, and take out the lower layer of viscous liquid, which is the composite surfactant component.
[0084] The preparation method of the silane coupling agent dispersion component is as follows:
[0085] Weigh 4 g of silane coupling agent KH-550 and disperse it in 200 ml of deionized water. Stir at a stirring speed of 600 r / min for 20 min to obtain the silane coupling agent dispersion component.
[0086] A preparation method of a composite liquid cement grinding aid, the preparation method comprising:
[0087] To 100 parts by weight of the silane coupling agent dispersion component, add 14 parts by weight of modified sodium lignin sulfonate, ultrasonically disperse at a frequency of 28 kHz for 30 minutes, then add 38 parts of polymer grinding aid solution, 9 parts by weight of modified triethanolamine and 4 parts by weight of the composite surfactant component, and stir at a stirring speed of 500 r / min for 30 minutes to obtain a composite liquid cement grinding aid.
[0088] Comparative Example 1
[0089] The composite liquid cement grinding aid and the preparation method thereof provided in this comparative example are substantially the same as those in Example 1, with the main difference being that in this comparative example 1, the polymer grinding aid solution in Example 1 is replaced with triethanolamine.
[0090] Comparative Example 2
[0091] The composite liquid cement grinding aid and the preparation method thereof provided in this comparative example are substantially the same as those in Example 1, with the main difference being that in this comparative example 2, the modified sodium lignin sulfonate in Example 1 is replaced by sodium lignin sulfonate.
[0092] Comparative Example 3
[0093] The composite liquid cement grinding aid and the preparation method thereof provided in this comparative example are substantially the same as those in Example 1, with the main difference being that the modified triethanolamine in Example 1 is replaced with triethanolamine in this comparative example 3.
[0094] Comparative Example 4
[0095] The composite liquid cement grinding aid and the preparation method thereof provided in this comparative example are substantially the same as those in Example 1, with the main difference being that the silane coupling agent dispersion component in Example 1 is replaced with deionized water in this comparative example 4.
[0096] Performance Testing
[0097] The composite liquid cement grinding aids prepared in Examples 1-3 and Comparative Examples 1-4 are marked as Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4, respectively. Then, the performance of Examples 1-3 and Comparative Examples 1-4 is tested. The specific testing methods and test items are as follows:
[0098] 1. The composite liquid cement grinding aids prepared in Examples 1-3 and Comparative Examples 1-4 were uniformly sprayed on the surface of the cement to be ground at a dosage of 0.01 wt %, and the specific surface area of the cement after different grinding times was recorded. The obtained data are recorded in Table 1;
[0099] 2. Referring to the standard of GB / T 17671-2021 "Test Method for Cement Mortar Strength (ISO Method)", the mechanical strength of cement after 30 minutes of grinding was tested by respectively adding the composite liquid cement grinding aid prepared in Examples 1-3 and Comparative Examples 1-4, and the obtained data are recorded in Table 2;
[0100] Table 1
[0101]
[0102]
[0103] Table 2
[0104]
[0105] It can be seen from the data in Table 1 that the cement mixed with the composite liquid cement grinding aid prepared in Examples 1-3 has a significantly higher specific surface area after grinding, indicating that the addition of polymer grinding aid solution, modified sodium lignin sulfonate, modified triethanolamine and silane coupling agent dispersion components to the composite liquid cement grinding aid in the present invention can significantly improve the grinding aid performance of the grinding aid, thereby better improving the surface properties of cement; it can be seen from the data in Table 2 that the cement mixed with the composite liquid cement grinding aid prepared in Examples 1-3 has higher compressive strength and flexural strength, indicating that the composite liquid cement grinding aid prepared in Examples 1-3 can improve the mechanical properties of cement.
[0106] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0107] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A composite liquid cement grinding aid, characterized in that: The composite liquid cement grinding aid is composed of the following components: a polymer grinding aid solution, modified sodium lignin sulfonate, modified triethanolamine, a composite surfactant component and a silane coupling agent dispersion component; The polymer grinding aid solution is prepared with maleic anhydride, triethanolamine, acrylic acid and isopentenyl polyoxyethylene ether as raw materials; The modified sodium lignin sulfonate is prepared by inserting a diethanolamine group into the structure of sodium lignin sulfonate; The modified triethanolamine is prepared by reacting succinic acid and triethanolamine as main raw materials; The composite surfactant component is prepared by reacting butyltriphenylphosphonium bromide and sodium dodecylbenzenesulfonate as main raw materials.
2. A composite liquid cement grinding aid according to claim 1, characterized in that: The preparation steps of the polymer grinding aid solution are: Step a, add 10g of maleic anhydride into a flask, stir in a water bath at 50°C until it melts, then add 15g of triethanolamine dropwise at a rate of 1 drop / s, keep warm in a water bath at 50°C for 2h, and cool to room temperature to obtain the functional monomer component; Step b, dissolving 11 g of acrylic acid in 20 g of deionized water, stirring until completely dissolved, the result is recorded as acrylic acid solution, dissolving 0.1 g of ammonium persulfate in 5 g of deionized water, stirring until completely dissolved, the result is recorded as initiator solution; Step c, add 60g of isopentenyl polyoxyethylene ether and 60g of deionized water into a flask, stir and dissolve in a 60°C water bath, and then simultaneously add the functional monomer component, acrylic acid solution and initiator solution at a rate of 2 drops / s. After keeping warm for 3 hours, the result is a polymer grinding aid solution.
3. A composite liquid cement grinding aid according to claim 2, characterized in that: The stirring speed for stirring until melting in step a is 500 r / min, the stirring speed for stirring until complete dissolution in step b is 300 r / min, and the stirring and dissolving operation in step c is stirring at a stirring speed of 200 r / min for 30 minutes.
4. A composite liquid cement grinding aid according to claim 1, characterized in that: The preparation steps of the modified sodium lignin sulfonate are: Step 1, add 10g sodium lignin sulfonate and 20g deionized water into a flask, stir thoroughly and add 11g diethanolamine, the result after ultrasonic treatment is recorded as the component to be reacted; Step 2, heat the components to be reacted to 70°C in a water bath and add 25g of formaldehyde solution at this temperature at a rate of 1 drop / s, reflux at a constant temperature for 2h, then cool to 45°C, remove deionized water by rotary evaporation, wash with anhydrous ethanol and filter to remove excess diethanolamine, dry the filter cake and grind it through a 200-mesh sieve to obtain modified sodium lignin sulfonate.
5. A composite liquid cement grinding aid according to claim 4, characterized in that: The operation of fully stirring in step 1 is stirring at a stirring speed of 400r / min for 10min, the operation of ultrasonic treatment in step 1 is ultrasonic dispersion at a frequency of 26kHz for 15min, the temperature of rotary evaporation in step 2 is 68°C, and the operation of drying in step 2 is drying in a vacuum drying oven at 60°C for 12h.
6. A composite liquid cement grinding aid according to claim 1, characterized in that: The preparation method of the modified triethanolamine is: Weigh the calculated amount of succinic acid and triethanolamine in a molar ratio of 1:3 and pour them into a flask. Add sulfuric acid solution dropwise under a water bath condition of 70-80°C to adjust the pH value to 4-5. After constant temperature reaction for 3-4 hours, cool to room temperature, add sodium hydroxide solution dropwise to adjust the pH value to 7, and the resulting product is modified triethanolamine.
7. A composite liquid cement grinding aid according to claim 1, characterized in that: In the preparation method of modified triethanolamine, the mass fraction of sulfuric acid solution is 10%, and the mass fraction of sodium hydroxide solution is 15%.
8. A composite liquid cement grinding aid according to claim 1, characterized in that: The preparation method of the composite surfactant component is: Weigh 5 g of butyltriphenylphosphonium bromide and 55 g of deionized water, mix them, add 4 g of sodium dodecylbenzenesulfonate, stir at a stirring speed of 600 r / min for 4 hours, let it stand for separation, and take out the lower layer of viscous liquid, which is the composite surfactant component.
9. A composite liquid cement grinding aid according to claim 1, characterized in that: The preparation method of the silane coupling agent dispersion component is: Weigh 3-5g of silane coupling agent KH-550 and disperse it in 200ml of deionized water. Stir at a stirring speed of 600r / min for 20min to obtain the silane coupling agent dispersion component.
10. A method for preparing a composite liquid cement grinding aid according to any one of claims 1 to 9, characterized in that: The preparation method is: 12-15 parts by weight of modified sodium lignin sulfonate are added to 100 parts by weight of silane coupling agent dispersion component, and after ultrasonic dispersion at a frequency of 28 kHz for 30 minutes, 35-40 parts by weight of polymer grinding aid solution, 8-10 parts by weight of modified triethanolamine and 3-5 parts by weight of composite surfactant component are added, and the mixture is stirred at a stirring speed of 500 r / min for 30 minutes to obtain a composite liquid cement grinding aid.
Citation Information
Cited By
Highway high-content smelting slag-based super sulfate cement and preparation method thereof
CN119977368A